The Analysis of Concept Mastering and Creative Thinking Skills of Prospective Physics Teachers Post-Online Learning During the Covid-19 Pandemic - Ahmad Busyairi; Muhammad Zuhdi; Muh. Makhrus (Jurnal Ilmiah Profesi Pendidikan, 2022)
The current era of globalization and technology confronts humans with new challenges and increasingly complex problems. Mastery of concepts and creative thinking skills are two of several competencies that must be possessed by almost all professions at this time. This study aims to determine the extent of mastery of concepts and creative thinking skills of prospective physics teachers on dynamic electricity. This research is descriptive researcher. The population of this study was 60 prospective physics teachers who were studying at the University of Mataram, West Nusa Tenggara, Indonesia. The number of samples used was 28 students who were taken using a simple random sampling technique. The instrument consists of cognitive tests at levels C1-C3 in the form of multiple choice and tests of creative thinking skills in the form of real-world problems that are open-ended so that they can allow students to provide many solutions to the problems given. There are four aspects of creative thinking skills used in this study, namely; fluency, flexibility, originality, and elaboration. The research data showed that 85.71% of students were able to correctly answer C1 cognitive level questions (remembering), 67.86% of students were able to solve C2 cognitive level questions (understanding), and 60.71% of students were able to solve questions C3 cognitive level questions (applying). Furthermore, for creative thinking skills, the fluency aspect is in the Moderate category with a score of 1.86, and flexibility is in the Low category with a score of 1.14. For aspects of Originality and Elaboration, students are included in the non-creative category with a score of 0.18 and 0.56.